Disproportionality of English Learners with Emotional and/or Behavioral Disorders: A Comparative Meta-Analysis with English Learners with Learning Disabilities. (May 2013) - Gage, Nicholas; Gersten, Russell; Sugai, George; Newman-Gonchar, Rebecca
Disproportionate representation of English learners in special education has been a longstanding and ongoing concern. However, research examining disproportionate representation of English learners receiving special education services for emotional and/or behavioral disorders (EBD) has been limited. To address this gap, a meta-analysis of disproportionate representation of English learners in the EBD category was conducted and the results were compared with same sample results for students receiving special education services for learning disabilities (LD). Based on five studies, the results of the meta-analysis indicate that English learners are disproportionately underrepresented in the EBD category generally and when compared with students in the LD category. Differences in odds ratios were found across educational contexts (i.e., school-level, district-level, state-level, and nationally), indicating different patterns of representation. Implications and potential reasons for disproportionality are discussed.